Animosity. Volume 4, The walled city - Bennett, Marguerite (Aftershock Comics, 2019)
Betrayal! Jesse is kidnapped by a traitor she trusted and loved. Sandor follows the bloody trail to the dreaded Walled City, where the remains of human civilization reign in terrible power<U+2015>and attempt to rebuild the world for humans only. With the hideous truth of the Walled City revealed, Sandor must use every ounce of cunning to rescue Jesse from her human captors<U+2015>before the try to "save the world" from the risen Animals...